2020
DOI: 10.15282/ijame.17.2.2020.07.0588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre and Post Weld Heat Treatment on the Mechanical Properties of Friction Stir Welded AA6061-T6 Joint

Abstract: This research work focuses on the study of the improvement of mechanical properties, specifically the tensile strength of 6061-T6 aluminum alloy on prismatic specimens with 9.5 mm thickness that has been subjected to friction stir welding process and two heat treatments; solubilized and aging before or after the welding process. Three cases studied and evaluated were, welding of the base material without heat treatment (BMW), solubilized heat treatment and partial aging of the base material before welding (HTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Studying FSWed joints of 6061-T6 alloy (Table 3), Juarez et al [316] reported that the surface fracture surfaces of tensile specimens, for the welding without heat treatment BMW and solubilized heat treatment and partial aging before welding HTBW cases, most of the fractures occurred on the AS of the tool and in the heat-affected zone. Fracture appeared on the unaffected material zone UFM and RS for the solubilized heat treatment and aging after welding HTAW case.…”
Section: Positioning Of Alloymentioning
confidence: 99%
See 4 more Smart Citations
“…Studying FSWed joints of 6061-T6 alloy (Table 3), Juarez et al [316] reported that the surface fracture surfaces of tensile specimens, for the welding without heat treatment BMW and solubilized heat treatment and partial aging before welding HTBW cases, most of the fractures occurred on the AS of the tool and in the heat-affected zone. Fracture appeared on the unaffected material zone UFM and RS for the solubilized heat treatment and aging after welding HTAW case.…”
Section: Positioning Of Alloymentioning
confidence: 99%
“…The FSWed joints of 6061-T6 alloy (Table 4), studied by Juarez et al [316] were obtained at constant TRS of 1000 rpm, WS of 90 mm/min, penetration speed of 9 mm/min, and holding time of 10 seconds. The last parameters allowed lowering the defects of welding.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
See 3 more Smart Citations